Protecting Children 'from Sex and Violence in the Media: - Marioll Hayes Hull Marioll Hayes Hull (Communicare)
Globally, governments are well aware of the political and social importance of the media and are developing policies aimed at regulating and controlling the media. In democratic societies, broadcast regulations generally focus on ensuring that broadcasters serve the public interest, needs and convenience. Also, over the past 2S years regulations have particularly focused on concerns related to children. In particular, there has been a universal concern over the growing amount of sex and violence in broadcast programming. Throughout the world, a growing number of nations are moving away from direct authoritarian control of media. Instead, they are moving toward combining government influence with free-market forces. For most governments the maintenance of some control includes ensuring the culture is not eroded by the sex and violence-filled products imported from countries like the United States, Great Britain, Mexico and others. Broadcasters believe attracting large audiences depends upon the purchase of quality programming from the increasingly lucrative international software market, even though the programs are filled with violence and sex. What are regulators doing to combat the growing problems associated with sex and violence in the media?